2008
DOI: 10.1007/s00221-008-1381-1
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin in the rat periventricular nucleus: sex differences and effect of gonadal steroids

Abstract: In the rat, the sexual dimorphism in growth hormone release is driven by sex steroids, and is suggested to result mainly from differences in somatostatin (SOM) release patterns from the median eminence. We studied the effect of gonadal steroids on SOM peptide-containing cells in the periventricular nucleus (PeVN) of ovariectomized (OVX) female rats, and compared these data with data from intact male rats. Adult female rats were treated with estradiol (E2) and/or progesterone (P), 3 months (long-term) or 2 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Estrogen did not affect total numbers of SOM-ir cells in the PeVN of young female rats in line with our previous studies (Van Vugt et al, 2008) and those of others (Estupina et al, 1996). Other studies reported a decrease in SOM mRNA content in the PeVN following OVX which was reversed by E 2 treatment Zorilla et al, 1991).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Estrogen did not affect total numbers of SOM-ir cells in the PeVN of young female rats in line with our previous studies (Van Vugt et al, 2008) and those of others (Estupina et al, 1996). Other studies reported a decrease in SOM mRNA content in the PeVN following OVX which was reversed by E 2 treatment Zorilla et al, 1991).…”
Section: Discussionsupporting
confidence: 90%
“…at ZT5 and ZT 11. Brains sections were stained for SOM peptide as described previously (Van Vugt et al, 2008).…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations